KONSEP E-DEMOCRACY PADA TATA KELOLA PEMERINTAHAN: STUDI KASUS PENERAPAN APLIKASI TANGERANG LIVE DALAM MEMBUKA PARTISIPASI PUBLIK - Linggar Vandito, Revo; Paramesti, Artanti; Ali Vardan Aminudin, Muhamad; Nurdin, Nurdin (Governance, 2025)
In the context of the Tangerang city government, the issue of public services and participation is still a problem in its implementation. There are several aspects related to services that must be improved and streamlined, such as licensing and investment services, education, agriculture and social services, especially service counters whose procedures and costs are not clear, hence the Tangerang Live application was created. The method used in this research is descriptive qualitative to provide a factual explanation of the facts that do exist in the field. The results of the survey conducted by the Tangerang City Information and Communication Office in 2023 obtained points of 80.87, indicating that the public was quite satisfied with the performance of the Tangerang Live application because it received a good indicator. In addition, the Tangerang Live application also succeeded in resolving 99.73% of the complaints made in the LAKSA feature. Thus, Tangerang Live has fulfilled the concept of e-government and increased participation through the available features